Controle da dinâmica Botton-up e Top-down do bacterioplâncton em reservatórios de região semiárida - Oliveira, Iara Bezerra de (2014)
There are several factors that influence the abundance and biomass bacterioplankton and their interactions in the plankton, among them, the inorganic and organic components, apart from the competition with phytoplankton and zooplankton predation by. Thus, the overall goal of this dissertation is to understand the dynamics of top-down and bottom-up control in bacterioplankton community structure in aquatic ecosystems located in the semiarid region. To this, were examined: i) the upward control (bottom-up) via the drivers of organic and inorganic bacterioplankton community biomass nutrients; ii) control by predation (top-down) and the competition in the semi-arid reservoirs through the relationship between communities (phytoplankton, bacterioplankton, zooplankton). Data were collected in the reservoir Poções and Camalaú, both located on the upper course of river Paraíba, Brazil. With fortnightly collections were conducted in two hydrological periods in 2012: April (dry season in the region) and June (rainy season in the region). In each shell collections occurred at two stations: Station 1- near the entrance of the main tributary (river Paraíba) and Station 2- next to the embankment of the reservoir and, at each station, water samples were collected for physical and chemical analysis and bacterioplankton, besides the realization of measures of primary productivity of phytoplankton. Zooplankton samples were collected by filtering 25 liters of water, plankton net. The data set shows that there is a positive correlation between the biomass of bacteria free and total phosphorus concentration (r 2 =0,14; p <0,05) , total nitrogen (r 2 = 0,10; p <0,05) and net primary production (r 2 = 0,14; p < 0,05) in the studied reservoirs. However, for shells with lower trophic level showed a strong negative correlation (r = -0,54; p< 0,05 ). The zooplankton groups, Rotifera and Cladocera showed a strong negative correlation with the biomass of bacterioplankton in the reservoirs of the semiarid region (r = -0,45; p< 0,05 ). The trophic status is an important factor in determining the dynamics and control of bacterioplankton community in the semiarid region reservoirs factor, where in eutrophic reservoirs considered a contole of combined (Bottom -up and Top -down) while on vessels with lesser degree occurs trophic who determines the biomass of the bacterial community is the bottom- up effect. We can conclude that the relationship between bacteria, phytoplankton and zooplankton in tropical systems are strong, but dependent on the type of aquatic system and its trophic state. Phytoplankton influences on bacterial dynamics through excretion of organic carbon and zooplankton through direct predation. In general, local factors such as availability of organic carbon, nutrients and presence of predators are sufficient to determine the structure of the microbial food web in the semiarid region systems.